1994
DOI: 10.1017/s0031182000078586
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent processes in the transmission of human onchocerciasis: intensity of microfilariae in the skin and their uptake by the simuliid host

Abstract: The transmission success of Onchocerca volvulus is thought to be influenced by a variety of regulatory or density-dependent processes that act at various points in the two-host life-cycle. This paper examines one component of the life-cycle, namely, the ingestion of microfilariae by the simuliid vector, to assess the relationship between intake of larvae and the density of parasites in the skin of the human host. Analysis is based on data from three areas in which onchocerciasis is endemic and includes publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In an analysis of data on the relationship between microfilaria uptake by the vectors and the density of microfilariae in the skin in human onchocerciasis from Guatemala (S. ochraceum s.l. ), West and Central Africa (Savanna members of the S. damnosum complex), and South Venezuela (S. guianense), it was concluded that microfilaria uptake by the vector hosts was not strongly density-dependent in the three geographical areas and the ranges of dermal microfilaria load examined [3]. Our results in the cattle/O.…”
Section: Discussionmentioning
confidence: 50%
“…In an analysis of data on the relationship between microfilaria uptake by the vectors and the density of microfilariae in the skin in human onchocerciasis from Guatemala (S. ochraceum s.l. ), West and Central Africa (Savanna members of the S. damnosum complex), and South Venezuela (S. guianense), it was concluded that microfilaria uptake by the vector hosts was not strongly density-dependent in the three geographical areas and the ranges of dermal microfilaria load examined [3]. Our results in the cattle/O.…”
Section: Discussionmentioning
confidence: 50%
“…When reported incubation period of biopsies was less than this, values were corrected according to standardized criteria 36 that had been successfully applied previously. 2 When mf burden was presented per skin snip (buttocks only), 31 an average weight of 2.0 mg/snip was used. 9 Because some investigators 30 gave only geometric means (iliac snips), their values are those presented by Dietz,9 who calculated arithmetic averages from the original data set at OCP headquarters.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to further understanding of such processes, a number of researchers have explored the properties of simple and complex mathematical models of the transmission dynamics of human onchocerciasis. 1 Considerable progress has been made concerning the regulatory constraints operating within the vector, [2][3][4][5][6] with some progress being recently made in investigating those acting within the human host. 7,8 A previous mathematical model 9 used an empirical relationship between the observed mean microfilarial (mf) load per milligram of skin per person in the community and the intensity of transmission in such a community, measured by the annual transmission potential (ATP).…”
Section: Introductionmentioning
confidence: 99%
“…It would have been possible to transform our mf counts to those obtained after a 24-h incubation in saline and to numbers of mf/mg as described in Basáñ ez et al (1994). This would have made little difference to our results, which can be seen as follows.…”
Section: Discussionmentioning
confidence: 99%